Nilai Pendidikan Karakter Tokoh Utama “Ava Alessandra” dalam Novel Heartbreak Motel Karya Ika Natassa (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the educational value of the main character Ava Alessandra in the novel Heartbreak Motel by Ika Natassa. The method that will be used in this study is the descriptive analysis method. The data in this study are in the form of quotes, clauses, and sentences that contain the educational values ​​of the main character Ava Alessandra in the novel. The data source is the novel Heartbreak Motel by Ika Natassa published by Gramedia Pustaka Utama in 2020 with a total of 400 pages. Data collection techniques consist of reading the novel, rereading, and marking relevant parts of the novel. Data analysis techniques involve interpretation, interpretation, determining character forms, grouping data, and description. The results and discussion show the character education value of Ava Alessandra in the novel, with a total of 88 data found, which include: honest character as many as 45 data, peace-loving character as many as 4 data, fear character as many as 3 data, friendly character as many as 4 data, hard-working character as many as 4 data, caring character as many as 10 data, religious character as many as 6 data, angry character as many as 6 data, appreciating achievement character as many as 5 data, and curiosity character as many as 1 data. It is also known that the most frequently appearing data is honest character data which amounts to 45 data, while the least frequently appearing data in the Heartbreak Motel novel by Ika Natassa is curiosity character data which amounts to 1 data